Managerial Incentives in a Stock Market Economy - Beck, Paul J.; Zorn, Thomas S. (Journal of Finance, 1982)
This study presents an analysis of the managerial incentive problem in a stock market economy in which incentive contracts are structured in terms of security ownership. In our model, the manager's ownership share signals effort and is determined endogenously as the solution to a special portfolio decision problem. Managerial investment in the firm is evaluated under various security pricing arrangements. Our analysis indicates that, in general, stockholders should sell shares to a manager at a discount to ensure a Pareto efficient ownership (incentive) structure. However, efficient pricing (discount) schedules generally are nonlinear and, in many respects, isomorphic to discriminating price functions which have been considered in neoclassical models of monopoly.